2018
DOI: 10.29303/jppipa.v5i1.174
|View full text |Cite
|
Sign up to set email alerts
|

THE CHARACTERISTICS OF YAM (Dioscorea Alata) STARCH EDIBLE FILM

Abstract: The purpose of this study was to determine the physical, mechanical and barrier properties of yam starch edible film. This research used Randomized Block Design (RAK).grouping the cultivar into 2, white and purple water yam. The starch concentration used were 1,33%, 2%, 2,67%, dan 3,33%.The results showed that the two cultivars produced similar properties of edible film.  The concentration of water yam starch affected transparency, thickness, water vapour transmision rate (WVTR) and compressive streght of edib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Increased concentrations of modified water yam starch tended to increase the thickness of the edible film (Figure 4). Ulyarti et al (2019) reported the thickness of edible film using water yam starch at a concentration of 2% at 0.117 mm, similar to the thickness of edible film from this current study with the addition of modified water yam starch up to 20%. This value is in accordance with established standards from the Japanese Industrial Standard (JIS) that edible films can be categorized as packaging materials if they have a maximum thickness of 0.25 mm.…”
Section: Edible Film Characteristicssupporting
confidence: 87%
See 2 more Smart Citations
“…Increased concentrations of modified water yam starch tended to increase the thickness of the edible film (Figure 4). Ulyarti et al (2019) reported the thickness of edible film using water yam starch at a concentration of 2% at 0.117 mm, similar to the thickness of edible film from this current study with the addition of modified water yam starch up to 20%. This value is in accordance with established standards from the Japanese Industrial Standard (JIS) that edible films can be categorized as packaging materials if they have a maximum thickness of 0.25 mm.…”
Section: Edible Film Characteristicssupporting
confidence: 87%
“…Thickness is one of the important parameters in edible film (Totosaus et al, 2020;Das et al, 2022). Aside of affecting its application on the product, it can also affect other parameters such as transparency, Water Vapor Transmission Rate (WVTR), solubility and compressive strength (Ulyarti et al, 2019). The edible thickness test is obtained from the average measurement of five different test points, including the corner and the middle of the edible film.…”
Section: Edible Film Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorbitol was used as a plasticizer. In terms of tensile strength, Canna edulis showed higher values, while for In addition, the degree of polymerization varies significantly among sources [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. There are some methods for fractionation, separation, and chemical modification to comply with edible films/coatings formulation.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…DiscussionThis study focused on the optimization of the development mixture of seaweed-based bioplastic. The commonly used method involves mixing 50.0 mL of deionized water per gram of biomass and optimizing the plasticizer content according to the raw material used(Daza et al, 2018;Nazarudin et al, 2018;Rahmawati et al, 2019). Instead of solely focusing on optimizing the glycerol content, this study also optimized the B: W ratio, which on a large industrial scale could help save costs on development while giving approximately the same quality bioplastics.…”
mentioning
confidence: 99%